Understanding Mars's Past Fluvial Geomorphology through Comparative Planetology - Studebaker-Reed, Mary (URJ-UCCS: Undergraduate Research Journal at UCCS, 2015)
There is no question that in the distant past, Mars was a planet teeming with liquid water, and the planet may have been hospitable enough to support life. The evidence of this past water is written all over Mars's dusty surface. The geomorphological features signal past fluvial activity. Using comparative planetology, such features can be compared to similar phenomena on Earth in order to draw conclusions regarding Mars' fluvial past and future.